First record of Piriqueta mexicana (Passifloraceae) for the flora of Chiapas, Mexico - Sánchez Molina, Diana Yaneth; Gómez Pérez, Ana Laura; Ramírez Marcial, Neptalí (Instituto de Ecología, A.C., 2020)
Background and Aims: The flora of Chiapas is one of the most diverse in Mexico, but there are still species that have not been described or registered. The objective of this study is to publish the presence of Piriqueta mexicana collected in the Protected Natural Area “La Concordia Zaragoza”.Methods: Botanical specimens of Piriqueta were collected and were determined taxonomically through the use of specialized keys, consultation of material in virtual collections and with expert taxonomists. In addition, morphometric measurements of petiole, leaves, flowers, fruits and seeds of the collected material were compared with the descriptions of the type specimen and taxonomic revisions.Key results: The presence of Piriqueta mexicana is confirmed for the flora of Chiapas; the number of Piriqueta species present in this entity is expanded to two.Conclusions: The distribution area of Piriqueta mexicana extends to southern Mexico and this finding reaffirms the importance of continuing with botanical explorations in Protected Natural Areas, which represent effective reservoirs to maintain poorly known species.